Pellino‐2 in nonimmune cells: novel interaction partners and intracellular localization. Issue 23 (12th November 2021) - Cristea, Ileana; Bruland, Ove; Aukrust, Ingvild; Rødahl, Eyvind; Bredrup, Cecilie
Abstract : Pellino‐2 is an E3 ubiquitin ligase that mediates intracellular signaling in innate immune pathways. Most studies of endogenous Pellino‐2 have been performed in macrophages, but none in nonimmune cells. Using yeast two‐hybrid screening and co‐immunoprecipitation, we identified six novel interaction partners of Pellino‐2, with various localizations: insulin receptor substrate 1, NIMA‐related kinase 9, tumor necrosis factor receptor‐associated factor 7, cyclin‐F, roundabout homolog 1, and disheveled homolog 2. Pellino‐2 showed cytoplasmic localization in a wide range of nonimmune cells under physiological potassium concentrations. Treatment with the potassium ionophore nigericin resulted in nuclear localization of Pellino‐2, which was reversed by the potassium channel blocker tetraethylammonium. Live‐cell imaging revealed intracellular migration of GFP‐tagged Pellino‐2. In summary, Pellino‐2 interacts with proteins at different cellular locations, taking part in dynamic processes that change its intracellular localization influenced by potassium efflux. Abstract : This study identified several new binding partners of Pellino‐2 that are localized in different intracellular compartments. In addition, a detailed localization study of Pellino‐2 in a variety of nonimmune cells, using subcellular fractionation, immunofluorescence, and live‐cell imaging experiments, revealed a dynamic localization of Pellino‐2, dependent on the intracellular K + concentration.